UJI KELAYAKAN PESAWAT SINAR-X TERHADAP PROYEKSI PA (POSTERO-ANTERIOR) DAN LAT (LATERAL) PADA TEKNIK PEMERIKSAAN FOTO THORAX - Miniati, Kadek; Sutapa, Gusti Ngurah; Balik Sudarsana, I Wayan (BULETIN FISIKA; Vol 18 No 1 (2017): BULETIN FISIKA, 2017)
Research has been conducted to determine feasibility test of the X-ray planePA and LAT projections on chest x-ray techniques. The study using a water phantom object as a substitute for patients with variations in interval distance ofthe  100-180 cm. Measurement of radiation dose X-rays performed five repetitions , measurable doses had be read on the device electrometer. Exposition factors to the PA projection using a tube voltage of 75 kV, current and time of 3,2 mAs, the irradiation field areaof (30 x 30) cm 2 .For the LAT projection tube voltage of 80 kV, current and time of 6,3 mAs, and the irradiation field area of (20 x 30) cm 2 . It the study of the radiation dose X-ray plane projection PA and LAT is optimal is below the limit value at the level of dosage guidelines BAPETEN No 08 of 2011. Obtained PA projections are below the value of 0,4 mGy while LAT projection is below the value of 1,5 mGy. The radiation dose X-rays plane using a variation of 100-180 cm distance is still below the dose limit values ??, thus meeting the objectives anssurance quality and quality control.